AN ANALYSIS OF NUMBER SENSE AND MENTAL COMPUTATION IN THE LEARNING OF MATHEMATICS - Aperapar, Parmjit Singh; Hoon, Teoh Sian (Jurnal Pengajaran MIPA, 2011)
The purpose of this research was to assess students’ understanding of number sense and mental computation among Form One, Form Two, Form Three and Form Four students. A total of 1756 students, ages ranging from 12 to 17 years, from thirteen schools in Selangor participated in this study. A majority (74.9%) of these students obtained an A grade for their respective year-end school examinations. The design for this study was quantitative in nature where the data on student’s sense of numbers was collected using two instruments, namely, Number Sense Test and Mental Computation Test. Each of these instruments consisted of 50 and 45 items respectively. The results from this study indicate that students were not able to cope to the Number Sense Test as compared to the Mental Computation Test. The former unveils a low percentage of 37.3% to 47.7% as compared to the latter of 79% to 88.6% across the levels. In the number Sense Test, surprisingly, there was no significant difference in the results between Form 1 students and Form 2 students and also between Form 3 students and Form 4 students. This seems to indicate that as the number of years in schools increase, there is an increasing reliance on algorithm and procedures. Although in the literature it has been argued that including mental computation in a mathematics curriculum promotes number sense (McIntosh et. al., 1997; Reys, Reys, Nohda, Emori, 2005), this was not the case in this study. It seems that an over reliance on paper and pencil computation at the expense of intuitive understanding of numbers is taking place among these students.